A Cognitive Theory of Trust - Claire A. Hill; Erin Ann O'Hara (Washington University Law Review, 2006)
Interpersonal trust is currently receiving widespread attention in theacademy. A fast-growing legal literature can draw insights from trust scholars in several other fields, including sociology, psychology, political science, economics, neuroscience, medicine, and management to explore the effects of legal policy on the nature of trust in interpersonal relationships. The issues are fundamental and worthy of more serious exploration: To what extent do legal rules, cases, and law enforcement efforts enhance or detract from the trust present in relationships? How can a better understanding of trust help us devise tools to improve human social and economic interactions?
Keywords: Corporations -- Corrupt practices; Health care reform; Trust; Cognitive psychology